2023
DOI: 10.1161/strokeaha.122.039793
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy Versus Best Medical Treatment in the Late Time Window in Non-DEFUSE-Non-DAWN Patients: A Multicenter Cohort Study

Abstract: Background: We assessed the efficacy and safety of mechanical thrombectomy (MT) in adult stroke patients with anterior circulation large vessel occlusion presenting in the late time window not fulfilling the DEFUSE-3 (Thrombectomy for Stroke at 6 to 16 Hours With Selection by Perfusion Imaging trial) and DAWN (Thrombectomy 6 to 24 Hours After Stroke With a Mismatch Between Deficit and Infarct trial) inclusion criteria. Methods: Cohort study of adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Furthermore, another important shortcoming affecting patient selection is the potential exclusion of some patients who could benefit from treatment due to the current restricted criteria [72] . This overselection was well described in two recent studies suggesting that the use of more permissive inclusion criteria could increase the number of patients treated with EVT in the late time window [73] , [74] . Lopez-Rivera and coworkers reported that the number of treatments with EVT in AIS patients with large vessel occlusion (LVO) admitted in both early and late time window was higher in centers with low advanced imaging utilization compared to those in which CTP was routinely used, without a significant increase in the incidence of poor outcome and hemorrhagic transformation [73] .…”
Section: Automated Selection In the Real Worldmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, another important shortcoming affecting patient selection is the potential exclusion of some patients who could benefit from treatment due to the current restricted criteria [72] . This overselection was well described in two recent studies suggesting that the use of more permissive inclusion criteria could increase the number of patients treated with EVT in the late time window [73] , [74] . Lopez-Rivera and coworkers reported that the number of treatments with EVT in AIS patients with large vessel occlusion (LVO) admitted in both early and late time window was higher in centers with low advanced imaging utilization compared to those in which CTP was routinely used, without a significant increase in the incidence of poor outcome and hemorrhagic transformation [73] .…”
Section: Automated Selection In the Real Worldmentioning
confidence: 85%
“…Lopez-Rivera and coworkers reported that the number of treatments with EVT in AIS patients with large vessel occlusion (LVO) admitted in both early and late time window was higher in centers with low advanced imaging utilization compared to those in which CTP was routinely used, without a significant increase in the incidence of poor outcome and hemorrhagic transformation [73] . More recently, Dittrich and colleagues showed that patients undergoing EVT at 6–24 h from onset and not satisfying DEFUSE 3 and DAWN inclusion criteria had an elevated probability to achieve a favorable outcome, without a higher frequency of symptomatic hemorrhagic transformation, compared to controls treated with best medical therapy [74] . In the attempt to further extend the patient population receiving EVT in the late time window, the opportunity of treating patients with large core were extensively explored [75] .…”
Section: Automated Selection In the Real Worldmentioning
confidence: 99%
“…The study period spans from January 2014 to May 2021. RESCUE EVT aims at assessing the role of endovascular stroke treatment beyond 6 h. 12 The study was approved in advance by the responsible cantonal ethics committee (ID 2020-00552).…”
Section: Methodsmentioning
confidence: 99%
“…3). 102 Interpretation should always start by assessing image quality metrics before evaluating the color maps. 72 Some important and frequent technical errors are due to patient motion, poor cardiac output, loss of intravenous access, truncation artifact/incomplete wash out, incorrect selection of Regions of Interest (ROIs).…”
Section: Journal Of Neurosonology and Neuroimagingmentioning
confidence: 99%